2021
DOI: 10.1109/jstars.2021.3080711
|View full text |Cite
|
Sign up to set email alerts
|

GEDI Elevation Accuracy Assessment: A Case Study of Southwest Spain

Abstract: Information about forest structures is becoming crucial to Earth's global carbon cycle, forest habitats and biodiversity. The Global Ecosystem Dynamics Investigation (GEDI) provides 25-m diameter footprints of the surface for 3D structure measurements. The main goal of this study is to compare 12 031 footprints of GEDI data with other airborne and spaceborne Digital Elevation Models (DEMs) for Southwest Spain. Ground elevation differences (ELM) are analyzed by comparing GEDI measurements with ALS LiDAR-and Tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 50 publications
(73 reference statements)
2
13
0
Order By: Relevance
“…An increasing residual error of GEDI terrain estimates on steep slopes is partly caused by geolocation error of GEDI samples of around 10 m for version 2 (Beck et al, 2021). Similar trends in increased GEDI residual errors with an increasing slope were observed in temperate forests of central Germany (Adam et al, 2020), in Mediterranean temperate forests of Southwest Spain (Quirós et al, 2021), in an alpine forest region of northern Italy (Kutchartt et al, 2022), in different ecozones across the United States (Liu et al, 2021) and across Eucalyptus plantations in Brazil (Fayad et al, 2021). Kutchartt et al (2022) reported that terrain slope is the most important factor influencing GEDI terrain height accuracy among other environmental (forest type, canopy cover) and sensor (beam sensitivity) parameters.…”
Section: Accuracy Of Gedi Terrain Height Estimatessupporting
confidence: 55%
“…An increasing residual error of GEDI terrain estimates on steep slopes is partly caused by geolocation error of GEDI samples of around 10 m for version 2 (Beck et al, 2021). Similar trends in increased GEDI residual errors with an increasing slope were observed in temperate forests of central Germany (Adam et al, 2020), in Mediterranean temperate forests of Southwest Spain (Quirós et al, 2021), in an alpine forest region of northern Italy (Kutchartt et al, 2022), in different ecozones across the United States (Liu et al, 2021) and across Eucalyptus plantations in Brazil (Fayad et al, 2021). Kutchartt et al (2022) reported that terrain slope is the most important factor influencing GEDI terrain height accuracy among other environmental (forest type, canopy cover) and sensor (beam sensitivity) parameters.…”
Section: Accuracy Of Gedi Terrain Height Estimatessupporting
confidence: 55%
“…In other words, only a fraction of the GEDI samples is captured by the model predictors, limiting the spectral representation of model predictors. Furthermore, the studies of Dorado-Roda et al, 2021 (european mediterranean forests) [69] and Quirós et al, 2021 (Southwest Spain) [70] highlight that there are certain limitations to GEDI-derived canopy height estimates and georeference. But limitations in GEDI-derived canopy height are specifically related to highly multilayered forest structures [69], which are only a minor proportion of the forests of the Paraguayan Chaco (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…While (2) subsumes many submodels, some of which are discussed in Section 5, the one we consider here is a model-based analog to several GEDI geolocation correction approaches, see, for example, Quirós et al (2021), Roy et al (2021), and, Blair and Hoften (1999). Again using the local coordinate system across all n observed locations, we estimate…”
Section: Submodelmentioning
confidence: 99%
“…Persistent geolocation errors may undermine forest canopy height retrievals in areas of complex or heterogeneous forest structure (Frazer et al, 2011; Milenković et al, 2017; Roy et al, 2021) and thus hinder identification of coincident measurements with field plot and ALS datasets (Duncanson et al, 2022). To this end, previous studies have implemented a variety of methods to characterize or even correct the geolocation uncertainty of spaceborne LiDAR data, including GEDI, and improve estimates of terrain and canopy heights, which are key covariates for forest AGB estimation (Liu et al, 2021; Quirós et al, 2021; Roy et al, 2021; Wang et al, 2022). In these studies, coincident ALS data with smaller geolocation errors are compared with spaceborne LiDAR measurements to assess disagreements between reported spaceborne RH metrics and observed ALS data, often via simulation to allow direct comparison.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation